Type V congenital pouch colon: An extremely rare variant of anorectal malformations - J D Rawat; Sudhir Singh; Nitin Pant; Digamber Chaubey (Wolters Kluwer Medknow Publications, 2017)
Type V is the rarest form of congenital pouch colon with only four cases reported till date. We report this anomaly in a 6-month-old boy. He was managed successfully with excision of distal pouch and coloplasty of proximal pouch along with abdominoperineal posterior sagittal anorectoplasty. We recommend preservation of proximal pouch in such cases.